2018
DOI: 10.18632/oncotarget.25007
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor: a potential therapeutic target for glioblastoma

Abstract: The median survival time of patients with glioblastoma is still poor (14.6 month), partly due to a lack of effective treatment.We have observed that androgen receptor (AR) is amplified in glioblastomas at the DNA, RNA and protein levels. The AR gene was amplified in 27% of glioblastoma specimens from men (n=22) and of 38.2% from women (n=21). AR-RNA was overexpressed (>2.5 fold) in 93% (n=30), and AR-protein was induced (>two fold) in 56% of the glioblastomas samples (n=16). Thirty percent of the glioblastomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(97 citation statements)
references
References 28 publications
6
89
2
Order By: Relevance
“…Our data confirm expression of the prostate cancer marker PSMA on microvasculature of glioblastoma, possibly providing opportunities for tumor-vascular targeting [55][56][57]. In a recent publication high expression levels of androgen receptor were described in glioblastomas, that actually translated into sensitivity to the AR antagonist enzalutamide [39]. Notably, our data also confirmed the identification of CA12v2 as a marker of poor prognosis in glioblastoma patients [58].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our data confirm expression of the prostate cancer marker PSMA on microvasculature of glioblastoma, possibly providing opportunities for tumor-vascular targeting [55][56][57]. In a recent publication high expression levels of androgen receptor were described in glioblastomas, that actually translated into sensitivity to the AR antagonist enzalutamide [39]. Notably, our data also confirmed the identification of CA12v2 as a marker of poor prognosis in glioblastoma patients [58].…”
Section: Discussionsupporting
confidence: 84%
“…SmMIPs were designed by an adjusted version of the MIPgen algorithm [37] and were ordered from Integrated DNA Technologies (Leuven, Belgium). The set of smMIP probes used in [34] was expanded with probes for detection of novel transcripts of interest that play a role in a wide variety of cancer types, including prostate cancer markers prostate specific membrane antigen (PSMA [38]) and androgen receptor and its splice variant ARv7 [39] (Table 1). Furthermore, smMIP probes were included for specific detection of splice variants by placing extension and ligation probes on neighboring exons, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that GBM biopsies overexpress AR, and that its levels are directly correlated to the astrocytomas grade. 13 , 14 , 16 Activation of AR by T induces migration, proliferation, and invasion of human GBM derived cell lines, 18 and in line with this, low levels of androgens are associated with a lower risk of glioma; 13 19 Finasteride (FIN) and dutasteride (D), both inhibitors of 5αR, have been proposed for GBM treatment. 20 , 21 Since T promotes GBM progression and it is converted into DHT (a more potent androgen), in this work we evaluated the effects of DHT, FIN, and D on proliferation, migration, and invasion of human GBM derived cell lines.…”
Section: Introductionmentioning
confidence: 89%
“…In line with these findings, an increased level of testosterone has been reported in patients with GBM [ 113 ]. In addition, androgen receptors are overexpressed in human GBM, and the genetic silencing of androgen receptors as well as their pharmacological inhibition, induce GBM cell death in vivo and in vitro [ 114 , 115 , 116 ]. Furthermore, the proliferation of GBM-derived cells was increased by testosterone, an effect that was antagonized by the androgen receptor antagonist flutamide [ 113 ].…”
Section: Role Of Tspo In Hallmarks Of Gbmmentioning
confidence: 99%